2010
DOI: 10.1002/chem.201001705
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of On‐Water Catalysis

Abstract: Sharpless and co-workers [1] used the term on-water to describe the substantial rate acceleration that is observed when some insoluble organic reactants are stirred in aqueous suspension. We now propose a mechanism that accounts for the phenomenon of on-water catalysis. Three of the observations of Sharpless and co-workers are directly pertinent to the mechanism we propose below. Firstly, the reaction mixture must be heterogeneous, that is, there must be an interface between the organic reactants and water. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 12 publications
5
90
2
1
Order By: Relevance
“…Structural complementarity between the probe and the iLBP should also influence activation efficiency, putatively accomplished by stabilization of the departing F − anion during the SuFEx reaction, thereby increasing the rate of conjugation. 1,25,27,2931,81 …”
Section: Resultsmentioning
confidence: 99%
“…Structural complementarity between the probe and the iLBP should also influence activation efficiency, putatively accomplished by stabilization of the departing F − anion during the SuFEx reaction, thereby increasing the rate of conjugation. 1,25,27,2931,81 …”
Section: Resultsmentioning
confidence: 99%
“…18 Recently, Aubry and co-workers developed two or three-liquid-phase microemulsion systems for the oxidation with singlet oxygen generated in situ; 19 Shapiro and co-workers successfully developed a metal-free system accomplishing aerobic oxidation of aldehydes on water. 21 We observe that reduction of the yield of imine with increase of the ratio of water to amine (Table 1, entries 5-8) most probably results from switching from ''on water'' to ''in water'' conditions where addition of 20 ml of water to the biphasic water (0.6 ml) and amine (0.6 mmol) suspension gives a homogeneous solution. 21 We observe that reduction of the yield of imine with increase of the ratio of water to amine (Table 1, entries 5-8) most probably results from switching from ''on water'' to ''in water'' conditions where addition of 20 ml of water to the biphasic water (0.6 ml) and amine (0.6 mmol) suspension gives a homogeneous solution.…”
mentioning
confidence: 85%
“…The present study raises a series of important photochemical, photophysical, and interfacial questions that are in general beyond the scope of electrochemical methodology. It is relevant that studies in acid-base behavior and catalysis in emulsions have also revealed the role that differences in structure play in the chemistry of water at interfaces (29)(30)(31)(32) (36). Structures of all ILs are provided in Fig.…”
Section: − Ilmentioning
confidence: 99%